Ethnobotany, diverse food uses, claimed health benefits and implications on conservation of barley landraces in North Eastern Ethiopia highlands - Sopade Peter A; Shewayrga Hailemichael (BMC, 2011)
Abstract Background Barley is the number one food crop in the highland parts of North Eastern Ethiopia produced by subsistence farmers grown as landraces. Information on the ethnobotany, food utilization and maintenance of barley landraces is valuable to design and plan germplasm conservation strategies as well as to improve food utilization of barley. Methods A study, involving field visits and household interviews, was conducted in three administrative zones. Eleven districts from the three zones, five kebeles in each district and five households from each kebele were visited to gather information on the ethnobotany, the utilization of barley and how barley end-uses influence the maintenance of landrace diversity. Results According to farmers, barley is the "king of crops" and it is put for diverse uses with more than 20 types of barley dishes and beverages reportedly prepared in the study area. The products are prepared from either boiled/roasted whole grain, raw- and roasted-milled grain, or cracked grain as main, side, ceremonial, and recuperating dishes. The various barley traditional foods have perceived qualities and health benefits by the farmers. Fifteen diverse barley landraces were reported by farmers, and the ethnobotany of the landraces reflects key quantitative and qualitative traits. Some landraces that are preferred for their culinary qualities are being marginalized due to moisture shortage and soil degradation. Conclusions Farmers' preference of different landraces for various end-use qualities is one of the important factors that affect the decision process of landraces maintenance, which in turn affect genetic diversity. Further studies on improving maintenance of landraces, developing suitable varieties and improving the food utilization of barley including processing techniques could contribute to food security of the area.